2015
DOI: 10.7727/wimj.2013.054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of General-epidural Anaesthesia on the Hemodynamics in Patients with Myasthenia Gravis

Abstract: Objective:The current study aims to explore the effects of general-epidural anaesthesia (GEA) on the perioperative haemodynamics in patients with myasthenia gravis (MG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…In the present study, patients undergoing CGEA took less time than those undergoing TIVA to recover spontaneous breathing, open their eyes on hearing whispered words and for tracheal extubation. Consistent with the current findings, Liu et al ( 41 ) demonstrated that the CGEA group had a shortened postoperative extubation time and recovery duration than the TIVA group. CGEA was reported to have the advantages of maintaining a normal hormone level, controlling blood pressure, maintaining hemodynamics and requiring less medication ( 42 44 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, patients undergoing CGEA took less time than those undergoing TIVA to recover spontaneous breathing, open their eyes on hearing whispered words and for tracheal extubation. Consistent with the current findings, Liu et al ( 41 ) demonstrated that the CGEA group had a shortened postoperative extubation time and recovery duration than the TIVA group. CGEA was reported to have the advantages of maintaining a normal hormone level, controlling blood pressure, maintaining hemodynamics and requiring less medication ( 42 44 ).…”
Section: Discussionsupporting
confidence: 91%